Multimode wave scattering problems in layered dissipative solids - Caviglia, G.; Morro, A. (Archives of Mechanics, 1999)
A general scheme within the frequency domain is elaborated for the scattering of obliquely-incident waves at a stratified, anisotropic, viscoelastic solid. Existence and uniqueness of the asymptotic wave propagator is established. Possible nonexistence of the scattering matrix at specific values of the incident field is then shown. Conditions for nonuniqueness or incompatibility of the direct scattering problem are provided.